Estudo comparativo de um experimento de eletrodinâmica: Laboratório Tradicional x Laboratório Remoto - Vilela, Douglas Carlos; Germano, José Silvério Edmundo; Monteiro, Marco Aurélio Alvarenga [UNESP]; Carvalho, Samuel José De [UNESP] (Sociedade Brasileira de Física, 2019)
This paper presents a comparative study of simple electrodynamics experiment, when performed in the Traditional Laboratory (TL) and in the Remote Laboratory (RL) via the internet. Analyze and validate the results, performing an statistical analysis of the learning gain, size of the applied methodology, reliability of the pre-test and post-test questionnaire and analysis of the variance of the students' responses. The research was applied with 304 students from five high schools in the city of Guaratinguetá in the state of São Paulo - Brazil. In order to maintain the fidelity of the study, the construction of the electrodynamic remote experiment was similar the traditional format. Students from each of the five schools were separated into classes A and B prepared a pre-test containing 10 questions for the selection of initial knowledge on the topic. In sequence, students in class A had access to the TL while those in class B to the RL to perform the experiment. At the end of the process, it was submitted to a test containing 10 questions to verify the knowledge after the experimental study. Final results had show equivalente learning between classes A and B in all schools analyzed.

Este artigo apresenta um estudo comparativo da aplicação de um experimento de física de eletrodinâmica básica, quando realizado num Laboratório Tradicional (LT) e num Laboratório Remoto (LR) via internet. Para analisar e validar os resultados, realizamos uma análise estatística do ganho de aprendizagem, tamanho do efeito da metodologia aplicada, confiabilidade do questionário de pré-teste e pós-teste e análise da variância das respostas dos estudantes. A pesquisa foi realizada com uma amostra de 304 alunos de cinco escolas distintas de ensino médio da cidade de Guaratinguetá do estado de São Paulo – Brasil. Para manter a fidelidade do estudo, a construção do experimento de eletrodinâmica foi a mesma, tanto no formato tradicional quanto no formato remoto. Os alunos de cada uma das cinco escolas, foram separados em turmas A e B e submetidos a um pré-teste contendo 10 questões para verificação do conhecimento inicial sobre o tema. Em sequência, os alunos da turma A tiveram acesso ao LT enquanto os da turma B ao LR para realização do experimento. Ao final do processo, foi aplicado um pós-teste contendo 10 questões para verificação do conhecimento após o estudo experimental. A estatística dos resultados mostrou resultados equivalentes entre as turmas A e B no processo de aprendizagem em todas as escolas analisadas.
Electrodynamics experiment comparative analysis: Real Lab vs Remote Lab
Keywords: Remote Lab; Traditional Lab; Electrodynamics; Ohms'law; Hit map; Laboratório Remoto; Laboratório Tradicional; Eletrodinâmica; Lei de Ohm; Mapa de acertos